A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae) - Moreira, Juan; Parapar, Julio (Zootaxa, 2015)
Moreira, Juan, Parapar, Julio (2015): A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae). Zootaxa 3911 (1): 91-105, DOI:10.11646/zootaxa.3911.1.5